Larval rearing of the spiny eel, Macrognathus aculeatus (Lacepede) under different rearing conditions: a preliminary study - Sahoo, S K; Giri, S S; Chandra, S; Sahu, A K (Indian Journal of Fisheries, 2011)
A study was carried out to evaluate the role of rearing conditions on growth and survival of the spiny eel, Macrognathusaculeatus (Lacepede) larvae during a 30 days experimental period. The study was conducted with three treatment groups: thefirst group was reared in fibre-glass tanks with 6" deep water (Treatment-1), the second group in tanks provided with floatingweed covering one fourth of the water surface (Treatment-2) and the third group was reared in tanks provided with soil bedand floating weed (Treatment-3). The tanks used for treatments 1 and 2 were not provided with soil bed. The growth andsurvival rate of the larvae, reared in the tanks with normal bottom and weed as well as in normal bottom without weed did notdiffer (p